Corneal scarring after epithelium-off collagen cross-linking - Radhika Natarajan; Divya Giridhar (Indian Journal of Ophthalmology, 2025)
Collagen cross-linking (CXL) is considered as a successful therapeutic approach for corneal conditions like keratoconus and corneal ectasia. Despite its efficacy in stabilizing these conditions, the occurrence of post-CXL scars remains a concern. Keratoconus and other corneal ectasias are characterized by structural weaknesses in the cornea. This weakness contributes to the vulnerability of corneal scar formation. In addition, corneal biomechanics and tissue properties play a significant role in scar development. Procedural factors during CXL, including duration and intensity of ultraviolet light exposure, the concentration and type of riboflavin, and the precise application of treatment, have been identified as potential causes of scar formation. Individual patient factors such as variations in healing response and genetic predispositions, associated ocular allergy, and chronic contact lens wear can also impact scar development post-CXL. Understanding these variables is essential for risk stratification and personalized treatment approaches, ultimately optimizing patient outcomes. In addition, regular follow-up visits and patient education are essential to ensure optimal healing and minimize scar related complications. We have tried to explain the numerous reasons of scarring following epithelium-off CXL by conducting a thorough Medline search and reviewing our clinical images. This review serves as a concise overview of the causes and risk factors associated with scar formation after epithelium-off CXL.